Nanoparticle-based drug delivery systems: An updated strategy for treating fungal keratitis - Guo, Yu Xiao; He, Yu Xi (Colloid and interface science communications, 2024)
Fungal keratitis is a globally blinding eye disease caused by fungi, with more than 1.05 million cases diagnosed annually, mainly in Asia. It is the most common form of infectious keratitis, accounting for approximately 40–50% of microbial keratitis cases. The disease is difficult to treat and the prognosis is often poor. Conventional antimicrobial therapies, which are the mainstay of treatment, face problems of off-target toxicity, low bioavailability, and drug-resistant fungi. In recent years, novel drug delivery systems have emerged as a promising alternative. These systems improve drug stability, extend drug residence time, control drug release, target specific tissues and cells, and reduce toxic side effects. Nanoparticle-based drug delivery systems are particularly compelling. The aim of this paper is to elucidate the mechanisms and advances of nanoparticle-based drug delivery systems in antifungal therapy and to provide new perspectives on the treatment of fungal keratitis. [Display omitted] •Summarize the pathogenesis of fungal keratitis.•Analyze the mechanisms and research progress of nanoparticle-based drug delivery systems in the study of antifungal keratitis drugs.